Evaluasi Penerapan Metode Pembelajaran Berpusat pada Mahasiswa (Student Centred Learning) pada Program Studi Ilmu Gizi Fakultas Kedokteran Masyarakat Universitas Hasanudin - Aminuddin Aminuddin; Gandes Retno Rahayu; Efrayim Suryadi (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2013)
Background: Shifting method from teaching to learning approaches require students to take the initiative to learn more, while academic staff only acts as a facilitator and requires them to be able to manage learning activities well. Thus it is necessary for them to know several methods of essential student centered learning so they can select the most suitable type of learning method to achieve the learning competencies from a single subject. The objective of this study is to evaluate academic staff knowledge, students of Nutrition Department, Faculty of Public Health class of 2008 and 2009 and supporting staff’s knowledge about student learning centered method.Method: This research was conducted with the mixed method (embedded design, qualitative research as part of the quantitative research) with a primary emphasis on quantitative research involving all students of class 2008 and 2009, who are still in the academic phase, academic staff of nutritional department and supporting staff of Faculty of Public Health, Hasanuddin University.Results: There are 3 methods most answer correctly by 54,5% of respondents that the advantages of using small group discussion, advantages of cooperative learning and problem based learning weaknesses. While the least correct answer is the advantage of problem-based learning method that is 4,5% respondents. For open questions, the most preferred methods are small group of, 18,2%; case studies of 18,2% and PBL of 13,6%. While the least preferred methods are cooperative learning and discovery learning 13,6%, respectively. This question is actually an open question so there were 27,3% of the respondents that did not answer; the preferred method or not.Conclusion: Respondents generally knew and heard the term SCL through correspondence, newspaper and faculty meetings. Respondents define SCL as learning with computers, in small rooms or some sort of FGD. In terms of the benefits of SCL respondents define it variously; to develop the potential and motivation of students, students more actively seek and accept; provide opportunities for students to obtain more sources, students find it easier to find lecture material”; student is more serious in his courses”; students more active in the lecture”; students are more self-sufficient“. Efforts made for the implementation of the SCL, according to in formant sare facilitating room equipments, props and LCD; expedite the administrative process; monitoring, inserting topics, and being ontime in the implementation of lecturers and improvementals of academic staff.